2022
DOI: 10.1088/1674-4926/43/11/112302
|View full text |Cite
|
Sign up to set email alerts
|

Ag-catalyzed GaSb nanowires for flexible near-infrared photodetectors

Abstract: High-quality narrow bandgap semiconductors nanowires (NWs) challenge the flexible near-infrared (NIR) photodetectors in next-generation imaging, data communication, environmental monitoring, and bioimaging applications. In this work, complementary metal oxide semiconductor-compatible metal of Ag is deposited on glass as the growth catalyst for the surfactant-assisted chemical vapor deposition of GaSb NWs. The uniform morphology, balance stoichiometry, high-quality crystallinity, and phase purity of as-prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 46 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…Here, high-quality GaSb NWs are pre-pared by using the surfactant-assisted chemical vapor deposition (CVD) method as previous reported. [37,38] The detailed growth process can be found in Experiment Section. From the scanning electron microscopy (SEM) image and X-ray diffraction (XRD) pattern in Figure S1 (Supporting Information), the as-prepared samples are uniform GaSb NWs with high density, smooth surface and pure zinc blende crystal structure (JCPDS Card No.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, high-quality GaSb NWs are pre-pared by using the surfactant-assisted chemical vapor deposition (CVD) method as previous reported. [37,38] The detailed growth process can be found in Experiment Section. From the scanning electron microscopy (SEM) image and X-ray diffraction (XRD) pattern in Figure S1 (Supporting Information), the as-prepared samples are uniform GaSb NWs with high density, smooth surface and pure zinc blende crystal structure (JCPDS Card No.…”
Section: Resultsmentioning
confidence: 99%
“…07-0215). [37][38][39] The details of solution-processed AlO x treated GaSb NW are then shown in Figure 1a. In short, after growth, GaSb NWs are dispersed and dipped in the precursor solution of Al(NO 3 ) 3 •9H 2 O and then transferred to the Si/SiO 2 substrates for a low-temperature combustion synthesis at 300 °C on a hotplate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Near-infrared (NIR) photodetectors have a significantly important practical value in the application fields of telecommunications, biosensing, medical imaging, space monitoring, etc. With the increasing demands for versatile optoelectronic applications, nanoscale photodetectors with superior detection performance, high sensitivity, and mechanical flexibility are extensively researched. In the past decade, one-dimensional semiconductor nanowires (NWs), especially III–V compound NWs, have attracted considerable research attention for high-performance photodetectors due to their high carrier mobility, large surface-to-volume ratio, direct bandgap, excellent flexibility, and superior photoresponsibility in photoelectric detection. In particular, ternary In x Ga 1– x As NWs are considered as promising candidates for integrated IR optoelectronic applications owing to their potential bandgap tunability from the NIR to the IR region (0.34–1.42 eV) at room temperature. However, the large number of unstable surface states on InGaAs NWs cause nonradiative (NR) emissions, delay the response time of the devices, and limit the photocurrent, which remains a problem that cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Infrared detectors can be categorized into photoconductive (including photogating effect), photovoltaic, photothermoelectric, bolometric, and pyroelectric detectors based on their operation principle . Notably, bolometric photodetectors can achieve wide spectral response at room temperature, which makes it widely used in infrared imaging, thermometry, and thermal accelerometers. The working principle of bolometric photodetectors is based on the changes in resistance of the sensing material with temperature upon light irradiation, which is characterized by the temperature coefficient of resistance (TCR). 2D materials have been found to possess large TCRs and a small heat capacity, which are thus promising candidates for use in high-performance bolometers. For example, Yuan et al demonstrated that high-quality graphene is an ideal high-speed bolometric material due to its broadband absorption, small heat capacity, and large TCR of approximately 1% K –1 .…”
Section: Introductionmentioning
confidence: 99%